Dose distribution and up‐titration patterns of metformin monotherapy in patients with type 2 diabetes. Issue 1 (17th December 2019) - Iglay, Kristy; Sawhney, Baanie; Fu, Alex Z.; Fernandes, Gail; Crutchlow, Michael F.; Rajpathak, Swapnil; Khunti, Kamlesh
Abstract: Aims: To assess the dose distribution among users of metformin monotherapy as well as the patterns of up‐titration following initiation of therapy in people with type 2 diabetes mellitus (T2DM). Materials and Methods: This was a retrospective cohort study of adults with T2DM in the United Kingdom (UK). Metformin dose distribution was assessed at 0, 6 and 12 months in people initiating metformin monotherapy (new users) and cross‐sectionally in people with ongoing metformin monotherapy (prevalent users). Patterns and predictors of up‐titration were also analysed in new users. Dose distributions and treatment patterns were assessed descriptively; predictors of up‐titration were determined using multivariable logistic regressions. Results: Totals of 6174 new users and 8733 prevalent users were included. New users initiated metformin at >0 mg to ≤500 mg (25%), >500 mg to ≤1000 mg (47%), >1000 mg to ≤1500 mg (17%) or >1500 mg to ≤2000 mg (12%) daily. This distribution did not vary over time. Prevalent users of metformin received doses of >0 mg to ≤500 mg (14%), >500 mg to ≤1000 mg (40%), >1000 mg to ≤1500 mg (15%), >1500 mg to ≤2000 mg (29%) or >2000 mg (1%) daily. Among new users of metformin, 6.7% and 10.8% had been up‐titrated at 6 and 12 months, respectively, despite the majority having glycated haemoglobin >53 mmol/mol. Predictors of up‐titration included younger age and higher HbA1c. Conclusions: A majority of T2DM patients taking metformin received a dose ≤1000 mg/day. Up‐titration of metformin is infrequent in the first year postinitiation. Abstract : This manuscript describes the initial and ongoing dose distribution of metformin in adults with diabetes in the UK, as well as the patterns of up‐titration over the year after initiation. We found that most patients are receiving a metformin dose lower than the minimum recommended level and that up‐titration of the starting dose was infrequent. This suggests that patients are undergoing regimen intensification before optimizing the metformin dose.